PENGELOLAAN STRES DALAM MENINGKATKAN PRESTASI AKADEMIK SISWA PADA MATA PELAJARAN AKIDAH AKHLAK - Desy Naelasari (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Academic stress is a psychological condition characterized by feelings of pressure experienced by students when academic demands do not align with their abilities and the expectations of parents, teachers, and their environment. This study aims to analyze stress management strategies in the learning of Akidah Akhlak and to identify the factors that contribute to improving students’ academic achievement at MTs Salafiyah Syafi’iyah Bandung Diwek Jombang. This research uses a descriptive qualitative approach with a field study method. Data were collected through participatory observation, in-depth interviews with relevant informants, and documentation to strengthen the validity of the findings. The results show that stress management in the learning process of Akidah Akhlak is implemented through three main strategies. First, cognitive restructuring by transforming students’ negative thinking patterns into positive ones through morning religious talks (kultum) and continuous motivational support. Second, structured time management using the Problem Disclosure Instrument (AUM) to identify students’ learning difficulties at an early stage. Third, the application of relaxation techniques through kinetic ice-breaking activities involving simple physical movements to reduce tension and create a more relaxed and conducive learning atmosphere. Furthermore, students’ academic achievement is influenced by both internal and external factors. Internal factors include teachers’ attention, guidance, and motivational support for students. Meanwhile, external factors involve the creation of a conducive learning environment through the use of varied teaching methods, the integration of technology such as projectors, the availability of adequate library resources, comfortable classroom facilities, effective school learning hours from 06:30 to 13:00, and the implementation of clear learning contracts between teachers and students to maintain discipline and academic focus.